2019
DOI: 10.1016/j.hrthm.2018.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Ablation compared with drug therapy for recurrent ventricular tachycardia in arrhythmogenic right ventricular cardiomyopathy: Results from a multicenter study

Abstract: Background: The comparative efficacy of antiarrhythmic drug therapy (AAD) versus ventricular tachycardia (VT) ablation in arrhythmogenic right ventricular cardiomyopathy (ARVC) is unknown. Objectives: We compared outcomes of AAD and/or beta blocker (BB) therapy to VT ablation (with AAD/BB) in ARVC patients with recurrent VT. Methods: In a multicenter retrospective study, 110 ARVC patients (38±17 years, 83% male) with a minimum of 3 VT episodes were included; 77 (70%) were initially treated with AAD/BB and 32 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 34 publications
1
16
0
3
Order By: Relevance
“…Fatal outcomes were all related to ARVC-related structural dysfunction, and we found no temporal association between VT recurrence and mortality or HT. These results are in line with a recent multicenter observational study finding no difference in survival in RFCAversus AAD-treated patients despite a significantly reduced VT burden in the former group 22 .…”
Section: Long-term Survival After Es In Arvcsupporting
confidence: 91%
“…Fatal outcomes were all related to ARVC-related structural dysfunction, and we found no temporal association between VT recurrence and mortality or HT. These results are in line with a recent multicenter observational study finding no difference in survival in RFCAversus AAD-treated patients despite a significantly reduced VT burden in the former group 22 .…”
Section: Long-term Survival After Es In Arvcsupporting
confidence: 91%
“…A retrospective study of 110 patients demonstrated CA of recurrent VT in patients with arrhythmogenic ventricular cardiomyopathy is no more effective than drugs but is more likely to be successful if both epicardial and endocardial approaches are used. 62…”
Section: Ablation Clinical Outcomesmentioning
confidence: 99%
“…Moreover, several studies have reported varying results on the procedural efficacy. [3][4][5][6][7][8][9][10][11][12] These studies have predominantly been conducted at large referral centers specialized in VT ablation and therefore the results may not reflect the general effect of VT ablation due to the selection and high volume in these centers. Therefore, the purpose of this study was to evaluate predictors and use of VT ablation and the post-procedural long-term outcome in a large multicenter cohort of patients with ARVC.…”
Section: Introductionmentioning
confidence: 99%